Determination Of Amoxicillin Residue In Cow Milk - Singh, S. K.; Sahni, Y. P.; Baghel, R.P.S.; Qureshi , S. R. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Antibiotics used as therapeutic agents or as feed supplement in milch animal lead to secretion of their residues into milk. Milk samples collected at day-0 (control), day-1, day-3 and day-5 after single IM administration of amoxicillin in 12 lactating cows showed significant level of residual concentration of amoxicillin on day-1. However, similar animals did not show any residual concentration of amoxicillin in milk samples collected on day-3 and day-5. The effect of pasteurization (LTLT) at 650C for 30 min on amoxicillin residue in milk was also evaluated. No significant (p>0.05) reduction of amoxicillin residue in milk was found on pasteurization.
Keywords: Amoxicillin; Pasteurization (LTLT); Milk; Residue